2023
DOI: 10.3389/fmed.2022.1029040
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of biosimilar TNF-alpha inhibitors uptake determinants in hospital environments in Italy, Portugal, and Spain

Abstract: BackgroundThe availability of biosimilar medicines in Southern European markets has allowed purchasing biologics at a lower cost for healthcare systems. However, the capacity to seize this cost-reduction opportunity in the long run depends on fostering a sustainable competitive environment for all the market players involved. Diverse policies and information campaigns have been launched in Italy, Portugal and Spain to support uptake of “best-value” biologics (BVB). Despite these measures, the utilization of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A study by Kim et al [ 33 ] found that demand-side policies used in the UK and France have been more effective than the supply-side price linking policy used alongside few demand-side policies, where the volume of the originator brand of infliximab actually increased. A study by Barcina Lacosta et al [ 34 ] lists the existence of policy frameworks that do not necessarily support the initiation of switching protocols as one of four key barriers to biosimilar uptake.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Kim et al [ 33 ] found that demand-side policies used in the UK and France have been more effective than the supply-side price linking policy used alongside few demand-side policies, where the volume of the originator brand of infliximab actually increased. A study by Barcina Lacosta et al [ 34 ] lists the existence of policy frameworks that do not necessarily support the initiation of switching protocols as one of four key barriers to biosimilar uptake.…”
Section: Resultsmentioning
confidence: 99%
“…If this study were replicated, it is hypothesised that consultants' responses would likely vary due to increased experience working with the pharmacy team. For instance, embedding a pharmacist in the gastroenterology inflammatory bowel disease standards and the practice of patient-centred care, which has successfully expanded into rheumatology and dermatology clinics, underscores the importance of pharmacist involvement [19,40,41]. Pharmacists, as medicinal product specialists, can mitigate barriers and dispel misconceptions about for other healthcare professionals and patients, potentially streamlining communication and improving adherence to treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Real-world data and publications of position statements from the Royal Colleges, British Society of Gastroenterology (BSG), British Society of Rheumatology (BSR), and British Association of Dermatology (BAD) also provide patients and consultants with reassurance [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, the ratio of biosimilar to reference drug users varies, often changing over time in favor of biosimilars [ 22 28 ]. This trend is most pronounced in countries where substitution is mandatory, and determined by tenders.…”
Section: Discussionmentioning
confidence: 99%
“…In order to encourage wider uptake of biosimilars, various countries are implementing different incentive systems [ 19 , 33 36 ]. Studies from various European countries, including Poland, show that the share of off-patent drugs is steadily decreasing, at the expense of more modern on-patent therapies [ 10 , 21 , 22 , 30 ]. While selecting the cheapest drug from the off-patent group guarantees its market share, there is no priority over other on-patent drugs, often with different modes of action.…”
Section: Discussionmentioning
confidence: 99%